ACYLCARNITINE PROFILE IN PRETERM SMALL FOR GESTATIONAL AGE INFANTS - Юдицкий, Антон Демитриевич (Mother and Baby in Kuzbass, 2025)
The study of the characteristics of carnitine metabolism and the profile of acylcarnitines in very premature infants born small and/or low for gestational age will allow the formation of a target group for therapeutic interventions and preventive measures in newborns and young children. The aim of the research – to establish the characteristics of the acylcarnitine profile during extended neonatal screening in premature infants born with small for gestational age body weight. Material and methods. The observation group included 19 premature infants with birth weight and/or length less than the 10th percentile for the given gestational age at birth according to the Intergrowth-21 scale (SGA), the comparison group included 74 examined infants with birth weight and/or length values greater than the 10th percentile (AGA). At the age of 144-168 hours of life, as part of the extended neonatal screening, capillary blood was collected from the heel for a test form. The concentration of carnitine and acylcarnitines was determined using tandem mass spectrometry. Statistical analysis of the parameters was performed using the nonparametric Mann-Whitney U-test and correlation analysis. Results. In the observation group, the concentration of octenoylcarnitine (0,18 [0,12; 0,19] μmol/l, p = 0,005), octanoylcarnitine (0,077 [0,068; 0,092] μmol/l, p = 0,012), decadienoylcarnitine (0,019 [0,015; 0,023] μmol/l, p = 0,005), 3-hydroxy-octadecadienoylcarnitine (0,035 [0,028; 0,038] μmol/l, p = 0,003), 3-hydroxy-octadecenoylcarnitine (0,034 [0,029; 0,041] μmol/l, p = 0,021) and hexacosanoylcarnitine (0,012 [0,012; 0,015] μmol/l, p = 0,009) significantly exceeded the indicators of the comparison group. The concentration of propionylcarnitine and tiglylcarnitine was significantly lower in those examined with SGA – 2,0 [1,3; 2,8] μmol/l (in the group of SGA children – 2,5 [1,8; 3,3] μmol/l, p = 0,029) and 0,018 [0,015; 0,023] μmol/l (in the comparison group 0,024 [0,018; 0,028] μmol/l, p = 0,04), respectively. Conclusion. Premature infants born small and low for gestational age have specific features of carnitine metabolism parameters in the early neonatal period. The nature of the acylcarnitine spectrum in very premature infants born small and low for gestational age should be taken into account when interpreting the results of extended neonatal screening, and the assessment of their clinical significance is the subject of further research in this area.